Optimal Precautionary Reserves for Low-Income Countries : A Cost-Benefit Analysis - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2011)
This paper develops a cost-benefit approach that helps to quantify the optimal level of international reserves in low-income countries, focusing on the role of reserves in preventing and mitigating absorption drops triggered by large external shocks. The approach is applied to a sample of 49 LICs over the period 1980-2008 to yield estimates of the likelihood and severity of a crisis. The calibration results suggest that the standard metric of three months of imports is inadequate for countries with fixed exchange rate regimes. The results also highlight the role of overall policy frameworks and availability of Fund-support in determining optimal reserve levels, raising questions about the uniform applicability of standard rules of thumb across countries.